Βιβλιοκρισία:D. KRALLIS, Michael Attaleiates and the Politics of Imperial Decline in Eleventh Century Byzantium, [Medieval and Renaissance Texts and Studies 422, Medieval Confluences Series 2], Tempe, Arizona 2012 - ΚΙΑΠΙΔΟΥ Ειρήνη - Σοφία (Byzantina Symmeikta, 2015)
Βιβλιοκρισία: D. Krallis, Michael Attaleiates and the Politics of Imperial Decline in Eleventh Century Byzantium, [Medieval and Renaissance Texts and Studies 422, Medieval Confluences Series 2], Tempe, Arizona 2012